Comparison of continuous erector spinae plane block and thoracic paravertebral block for postoperative analgaesia in patients undergoing modified radical mastectomy: A randomised controlled non-inferiority trial - Lovepriya Sharma; Pradeep Bhatia; Sadik Mohammed; Priyanka Sethi; Swati Chhabra; Mritunjay Kumar (Indian Journal of Anaesthesia, 2023)
Background and Aims: Modified radical mastectomy (MRM) is associated with significant postoperative pain for which many blocks including thoracic paravertebral (TPV) block are being used. Erector spinae plane (ESP) block is a recently described technique. We planned to compare the efficacy and safety of ultrasound-guided continuous ESP and TPV blocks for postoperative analgaesia following MRM. Methods: Sixty-six patients belonging to American Society of Anaesthesiologists physical status I and II, aged 25–85 years, undergoing MRM were enrolled and randomly allocated into two groups. Ipsilateral block was given preoperatively at T3 or T4 level with 20 ml of 0.5% ropivacaine and 50 μg fentanyl. Infusion of 0.5% and 0.2% ropivacaine with fentanyl 2 μg/ml at a rate of 5 ml/hr was continued during intraoperative and postoperative period, respectively. Pain was assessed using visual analogue scale (VAS) till 24 hours. Block performance time, time to first rescue analgaesia, total amount of rescue analgaesic consumed, the incidence of procedure-related and postoperative complications, failure rate and patient satisfaction score were also recorded. Data collected were analysed using the Chi-square test or Student's t-test with the help of SPSS 22.0. Results: Demographics, baseline vitals, VAS scores both at rest and on movement, block performance time, time to first rescue analgaesia, the total amount of rescue analgaesia and patient satisfaction score were comparable in both groups (P value > 0.05). No complications were observed in either group. Conclusion: In patients undergoing MRM, continuous catheter technique ESP block is as efficacious and safe as TPV block for providing prolonged postoperative analgaesia.